Premature Deaths Attributable to the Consumption of Ultraprocessed Foods in Brazil - De Moraes-Ferrari, G (Elsevier Inc., 2023)
Introduction: Ultraprocessed foods have been associated with an increased risk of noncommunicable diseases, such as diabetes, cardiovascular diseases, and cancer as well as all-cause mortality. The study aimed to estimate premature deaths attributable to the consumption of ultraprocessed food in Brazil. Methods: A comparative risk assessment model was developed on the basis of RRs from a recent meta-analysis, national food consumption for 2017–2018, and demographic and mortality data for 2019. Population attributable fractions for all-cause mortality were then estimated within each sex and age stratum according to the distribution of the ultraprocessed food contribution to the total energy of the diet. Analysis was conducted in February 2022–April 2022. Results: The contribution of ultraprocessed foods to the total energy intake of the diet across sex and age stratum of Brazilian adults ranged from 13% to 21% of the total energy intake. A total of 541,160 adults aged 30‒69 years died in 2019. The consumption of ultraprocessed foods was responsible for approximately 57,000 premature deaths (95% uncertainty interval=33,493, 82,570) or 10.5% of all premature deaths in adults aged 30‒69 years. Reducing the contribution of ultraprocessed foods to the total energy intake by 10%‒50% could potentially prevent 5,900 deaths (95% uncertainty interval=2,910, 10,613) to 29,300 deaths (95% uncertainty interval=16,514, 44,226), respectively. Conclusions: The consumption of ultraprocessed foods represents a significant cause of premature death in Brazil. Reducing ultraprocessed food intake would promote substantial health gains for the population and should be a food policy priority to reduce premature mortality. © 2022 American Journal of Preventive Medicine